Revisiting Legal and Ethical Challenges in Fulfilling Human Right to Clean Air in Indonesia - Detania Sukarja; Barran Hamzah Nasution (Jurnal HAM, 2022)
Pro-investment and development government policies to achieve people's welfare can potentially violate human right to clean air through business activities that contribute to air pollution. In Jakarta, this condition led to a public lawsuit against the central and regional governments, who were considered liable for the air pollution and harm suffered by the community. This study reviews the concept of the right to clean air as a human right and analyzes the legal and ethical challenges in fulfilling human right to clean air in Indonesia. The discussion includes the relationship between business and human rights, the concept of clean air as a human right and a review of the legal framework to enforce liability and accommodate legal remedies and the private initiatives to drive and implement more responsible choices to reduce air pollution. The method used in this study was a literature study with data analyzed qualitatively. The paper concludes that people's right to clean air is a fundamental human right. The fulfillment of human right to clean air can be driven by state's power to impose regulation and the implementation of ethical and responsible business activities by corporations. The government needs to strengthen regulations related to air pollution control and business legal compliance, notably strengthening applicable air quality standards in accordance with evidence-based, internationally recognized standards to protect public health. Similarly, corporations should act as "moral agents" who apply ethical behaviors in their business activities to minimize air pollution.